Quando as tecnologias embaralham nossas vidas: as nanotecnologias - Marcos Nalli (Estudios Sociales)
Despite the obvious scientific and technological advances, the use of nanostructured products can be highly beneficial or harmful to any living being. There are risks, but there are also promises ... Therefore, it is urgent to interpret ethics of nanotechnology: not a moral discourse on 1 Esse artigo é uma das atividades desenvolvidas no projeto de pesquisa "Nanociência e Nanotecnologia aplicadas às ciências da vida: Bases epistêmicas, impasses éticos", financiado pelo CNPq (Processo 400778/04-1), entre os anos de 2004 e 2006. Sua versão atual - até então inédita - se dá como parte das atividades desenvolvidas em meus estágio pós doutoral, durante o ano de 2008, no Centre de Recherche Historique - École des Hautes Études en Sciences Sociales, Paris - França, com o apoio financeiro da Capes (processo 0606/07-3), Brasil. Meus sinceros agradecimentos ao parecerista, por suas preciosas observações; contudo, todas as limitações deste artigo são de minha inteira e exclusiva responsabilidade. "rights", thinking in categories of good and evil, and formulating deontological rules. Nanotechnologies help to think what is the status of living beings, especially human beings, based on binomial - often misunderstood and misinterpreted - of the artificiality and nature: their interaction is characterized primarily in the human ability (that nanotechnology only radicalizes) for the transformation of their environment.